Dietary Protein-Induced Changes in Archaeal Compositional Dynamics, Methanogenic Pathways, and Antimicrobial Resistance Profiles in Lactating Sheep - Maida Mushtaq; Xiaojun Ni; Muhammad Khan; Xiaoqi Zhao; Hongyuan Yang; Baiji Danzeng; Sikandar Ali; Muhammad Hammad Zafar; Guobo Quan (Microorganisms)
Dietary protein levels greatly influence gut microbial ecosystems; however, their effects on gut archaea and associated functions in ruminants require further elucidation. This study evaluated the impact of varying dietary protein levels on gut archaeal composition, antimicrobial resistance (AMR) genes, virulence factors, and functional capacities in sheep. Eighteen ewes (Yunnan semi-fine wool breed, uniparous, 2 years old, and averaging 50 ± 2 kg body weight) were randomly assigned to diets containing an 8.5 (low; H_1), 10.3 (medium; H_m), or 13.9% (high; H_h) crude protein level from the 35th day of pregnancy to the 90th day postpartum. The total duration of the experiment was approximately 202 days. A total of nine fecal samples (three from each group) were analyzed via 16S rRNA and metagenomics sequencing. Higher archaeal alpha diversity and richness were observed in the H_m and H_h groups compared to the H_l group (p < 0.05). A Beta diversity analysis revealed the archaeal community’s distinct clustering mode based on protein levels. The methanogenic genera Methanobrevibacter and Methanocorpusculum were dominant across the three groups, and their abundance was influenced by protein intake. A functional prediction analysis indicated moderate changes in amino acid and carbohydrate metabolism, which are particularly associated with methane production, an important source of greenhouse gases. AMR genes (e.g., tetA (60), patA, vat, and Erm methyltransferase) and virulence factors (Bacillibactin, LPS) were significantly enriched when animals were fed high-protein diets. Our results demonstrated that dietary protein levels significantly influence gut archaeal composition, AMR gene enrichment, and related functional pathways. Medium-protein diets promoted greater archaeal diversity, whereas high-protein diets favored resistance gene proliferation and enhanced methanogenic activity. Optimizing dietary protein intake may enhance gut health, mitigate antimicrobial resistance risk, and reduce methane emissions, thereby supporting livestock sustainability and environmental protection.